Isolation and sequence of the gene for actin in Saccharomyces cerevisiae. - Ng, R (1980)
The yeast Saccharomyces cerevisiae is known to contain the highly conserved and unbiquitous protein actin. We have used cloned actin sequences from Dictyostelium discoideum to identify and clone the actin gene in yeast. Hybridization to genomic fragments of yeast DNA suggest that there is a single actin gene in yeast. We have determined the nucleotide sequence of that gene and its flanking regions. The sequence of the gene reveals an intervening sequence of 309 base pairs in the coding sequences at the 5' end of the gene. The existence and location of the intervening sequence was verified by using the dideoxy chain termination technique to determine the sequence at the 5' terminus of the actin mRNA. The similarity of the splice junction sequences in this gene to those found in higher eukaryotes suggests that yeast must possess a similar splicing enzyme.